Cinética de aquecimento e secagem, propriedades dielétricas e simulação computacional aplicado ao tratamento de cascalho de perfuração por microondas - Rossi, Arley Silva (2017)
Cutting from the drilling process and contaminated with non-aqueous drilling fluids are tailings from the oil industry and have gained a attention as environmental laws that control their disposal are increasingly severe. Microwave heating and drying to promote the removal of these contaminants has been studied over the past few years and has been shown to be a promising technology. The kinetics of heating and drying, the penetration depth of electromagnetic radiation, as well as the interaction of the electromagnetic field with the material to be heated are directly associated with the dielectric properties. In addition, the mathematical modeling and numerical simulation of microwave heating and drying operations are strongly dependent on these properties. Thus, the present work aims to evaluate the dielectric properties of the drilling cuttings. Moreover, the present work also investigated the fundamental aspects of the kinetics of heating and drying of cuttings by microwave. To understand the influence of the major components present on the contaminated cuttings, heating curves of components of the cuttings/fluid mixture were individually evaluated. Some classical models of conventional drying of solids were used to describe the kinetics of removal of the fluids present in these contaminated cuttings. Finally, the knowledge of the dielectric properties and the kinetics of heating and drying of the cuttings was used in an electromagnetic simulation process. For this, commercial software was used in order to perform computational simulations to compare the calculated dielectric properties and qualitatively describe the heating operation of the blends evaluated in the present work. In this way, through the results obtained, it was possible to better understand the interaction of the dielectric properties associated to cuttings granulometry and the concentration of contaminants, through the drilling fluid. The kinetic study of heating and drying comprised important aspects related to the interaction of water with the components of the cuttings/fluid mixture, as well as the heating of the solid, evaporation of this water and entrainment of organic bases. The computational simulation showed a strong connection of the dielectric properties with the absorption of energy, through the formation of the electric field, and the dissipation of this energy in the form of heat. Therefore, these results are of great relevance for the improvement and development of improvements in the operation of microwave decontamination, ensuring a fast and effective treatment with low energy costs.